Early Clinical Diagnosis and Treatment of Traumatic Aortic Injury Caused by Thoracic and Abdominal Injuries: A Series of Four Cases with Literature Review. (30th April 2021) - Wu, Qiqi; Sun, Shanshan; Xie, Jie; Li, Tianyu; Li, Hui; Bai, Xiangjun; Li, Zhanfei; Wang, Wei
Abstract : Aortic injury, particularly traumatic aortic dissection caused by thoracic and abdominal injuries, is extremely rare. The diagnosis rate of blunt aortic injury caused by chest and abdominal injuries is often low, and its clinical manifestations are atypical. Once missed or misdiagnosed, the consequences are serious. Early diagnosis of traumatic aortic injury in complex thoracic and abdominal injuries is a key factor in reducing the mortality of trauma patients. Among all trauma patients treated in our department from December 2018 to December 2020, we diagnosed four cases of aortic injury, including three cases of aortic dissection and one case of intramural hematoma. Successful surgical treatment and clinical outcome were achieved in all four patients. We found that early diagnosis and surgical treatment can help to reduce the mortality of patients with traumatic aortic injury and improve the prognosis.